Prostat Kanseri - Altıntaş, Yunus Emre; Yıldırım, Sedat; Teksöz, Duygu; Kıdı, Mehmet Mutlu; Merç Çetinkaya, Ayşegül; Karaca, Mustafa; Akçay Çelik, Mürüvvet; Gökoğlu, Mustafa; Şişman, Ali Fırat; Börekoğlu, Ali; Ünal, Öznur; Aydınalp Camadan, Yasemin; et al. (2023)
-